2021
DOI: 10.1080/10717544.2021.1917729
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, and in vitro and in vivo evaluation of etomidate intravenous lipid emulsion

Abstract: The aim of this investigation was to develop an etomidate intravenous lipid emulsion (ETM-ILE) and evaluate its properties in vitro and in vivo . Etomidate (ETM) is a hydrophobic drug, and organic solvents must be added to an etomidate injectable solution (ETM-SOL) to aid dissolution, that causes various adverse reactions on injection. Lipid emulsions are a novel drug formulation that can improve drug loading and reduce adverse reactions. ETM-ILE was prepared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The homogenization or sonication of the mixture in water creates an emulsion ideal for delivering hydrophobic drugs such as propofol. 33,35,[41][42][43] Johnson et al, used soy phosphatidylcholine, glycerol dioleate, and polysorbate to create a lipid crystal nano emulsion with a particle size around 118 nm. 33 The propofol 25…”
Section: Encapsulation Of Propofol In Lipid Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The homogenization or sonication of the mixture in water creates an emulsion ideal for delivering hydrophobic drugs such as propofol. 33,35,[41][42][43] Johnson et al, used soy phosphatidylcholine, glycerol dioleate, and polysorbate to create a lipid crystal nano emulsion with a particle size around 118 nm. 33 The propofol 25…”
Section: Encapsulation Of Propofol In Lipid Nanoparticlesmentioning
confidence: 99%
“…50 Finally, intravenous lipid emulsions were developed and exhibited a similar Nanoscale Advances Review pharmacokinetic prole to commercial etomidate as it showed low haemolysis but with low vascular irritation. 41…”
Section: Solid Lipid Nanoparticles (Sln)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pain on injection, venous irritation, and hemolysis were virtually abolished by the new fat emulsion preparation of etomidate. 4 but it failed to reduce the incidence of myoclonus. Myoclonic movements after etomidate injection develop in nearly 80% of the non-pre-medicated patients which may lead to regurgitation and aspiration in the non-fasting patients, may even raise the risk of prolapse of the vitreous in patients with open globe injury.…”
Section: Introductionmentioning
confidence: 99%
“…PCA and Design of experiments (DoE) have been proved as extremely utile tools for the construction of design spaces, an important component of control strategy for QbD [8][9][10][11][12]. Central composite design is the most frequently used design in the response surface optimization technique [13][14][15][16]. Prazosin HCl (PZH) is a sympatholytic drug used to treat high blood pressure, anxiety and post-traumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%